Facile synthesis of iron-ruthenium bimetallic oxide nanoparticles on carbon nanotube composites by liquid phase plasma method for supercapacitor - Lee, Won-June; Jeong, Sangmin; Lee, Heon; Kim, Byung-Joo; An, Kay-Hyeok; Park, Young-Kwon; Jung, Sang-Chul (The Korean journal of chemical engineering, 2017)
Iron-ruthenium bimetallic oxide nanoparticles were precipitated on carbon nanotubes by liquid-phase plasma method. We also evaluated the physicochemical and electrochemical properties of prepared composite for supercapacitor electrode. Polycrystalline about 10 to 25 nm-sized bimetallic nanoparticles were evenly precipitated on the carbon nanotube (CNT) and consisted of Fe 3+ and Ru 4+ . Bimetallic oxide nanoparticles’ composition depended on the ratio of the metal precursor concentration and standard reduction potential. The C-V area and specific capacitance of iron-ruthenium oxide nanoparticle/carbon nanotube (IRCNT) composite electrodes was higher than that of untreated CNT electrode, and increased with increasing ruthenium content. The cycling stability of IRCNT composite electrode was higher than untreated CNT electrode, especially iron element was more stable.